Cytotoxic effects of permethrin on mouse liver and spleen cells - Roma, Gislaine Cristina [UNESP]; De Oliveira, Patricia Rosa [UNESP]; Bechara, Gervasio Henrique [UNESP]; Camargo Mathias, Maria Izabel [UNESP] (Wiley-Blackwell, 2012)
This study analyzed the histopathological and histochemical effects of different dosages of permethrin on liver and spleen cells of mice, in order to evaluate the toxic potential of this substance and the possible impairments that this chemical causes in different tissues of nontarget organisms (laboratorial conditions). The results showed that permethrin caused severe alterations in the liver cells, reducing the size of the nuclei and causing hydropic degeneration of the hepatocytes, in addition to stimulating the proliferation of Kupffer cells, altered the amount of proteins, polysaccharides, lipids, and vacuoles in the cytoplasm of the hepatocytes and congested the hepatic capillaries. As for the spleen of the treated mice, no alterations were observed in the morphology in relation to the control group, what would suggest that the spleen would continue performing its functions, without suffering morphological alterations even in the presence of the toxic agent. Microsc. Res. Tech., 2011. (c) 2011 Wiley Periodicals, Inc.
Keywords: Mice; Permethrin; Cytotoxicity; Histopathology